Accounting Information System Web Based in Middle School Muhammadiyah 3 Bandung - Endang Amalia; Dior B. Gunawan (Politeknik Pertanian Negeri Samarinda, 2020)
This study aims to help solve accounting problems in the Muhammadiyah 3 junior high school where the research was conducted. The background of writing this report is because there are some problems that exist around accounting management including the work of financial employees who are still ineffective and inefficient, making reports that require an iterative process and employee service to parents of students. Research data collection through the process of library research and the process of interviews with financial employees. The research method used is the action reaserch and the method of development is the Unified Software Development Process while the system modeling using the Unified Modeling Language is expected to maximize the desired results. Research carried out includes making a web-based financial information system in Muhammadiyah 3 junior high school including several factors, namely data management systems ranging from employee data, students, student finance, income, expenses and there is also making financial reports using a codeigniter framework. It is hoped that the development of web-based information systems can overcome the existing accounting problems.